2022
DOI: 10.3389/fclim.2022.925068
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of sea surface temperature anomalies at the eastern pole of the Indian Ocean Dipole—using a convolutional neural network model

Abstract: In this study, we train a convolutional neural network (CNN) model using a selection of Coupled Model Intercomparison Project (CMIP) phase 5 and 6 models to investigate the predictability of the sea surface temperature (SST) variability off the Sumatra-Java coast in the tropical southeast Indian Ocean, the eastern pole of the Indian Ocean Dipole (IOD). Results show that the CNN model can beat the persistence of the interannual SST variability, such that the eastern IOD (EIOD) SST variability can be forecast up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Ratnam et al (2020) proposed an FCN to forecast SSTAs and the IOD oscillation over the Indian Ocean. Also, the IOD forecasts have been made using an LSTM (Pravallika et al, 2022) and a CNN (Feng et al, 2022). Moreover, a CNN was developed to forecast SSTs and marine heatwaves around Australia (Boschetti et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Ratnam et al (2020) proposed an FCN to forecast SSTAs and the IOD oscillation over the Indian Ocean. Also, the IOD forecasts have been made using an LSTM (Pravallika et al, 2022) and a CNN (Feng et al, 2022). Moreover, a CNN was developed to forecast SSTs and marine heatwaves around Australia (Boschetti et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…The heatmaps are extracted from the best ensemble member among the top ten. These heatmaps have been proposed by Selvaraju et al (2020) and were further found useful for estimating the relative contribution of the predictors in a few recent past studies (Liu et al, 2021;Feng et al, 2022). Equation (3) elaborates on the estimation of activation maps for specific convolutional layers (Krizhevsky et al, 2012) and Equation ( 4) elaborates on the extraction of gradients from a specific layer (Selvaraju et al, 2020).…”
Section: Heatmapsmentioning
confidence: 99%
“…Therefore, in the current study, we propose a forecasting scheme for ENSO at very long lead times (up to 3 years) based on CNN by additionally taking into account the varying parameters of CNN models for each season and training them with a customized loss function which considers extreme ENSO events separately. This is a kind of a novel attempt compared to previous studies of deep learning applied to climate predictions (Ham et al, 2019(Ham et al, , 2021bGeng and Wang, 2021;Hu et al, 2021;Liu et al, 2021;Mu et al, 2021;Feng et al, 2022). We train the CNN models using the past monthly global sea-surface temperature anomalies (SSTA) and vertically averaged subsurface ocean temperature anomaly (VATA) (averaged over 0-300 m depth, a proxy for heat content) fields.…”
Section: Introductionmentioning
confidence: 99%
“…The larger the gradients from a specific region the stronger the control it has over the variability 32 . The gradient heatmaps 32 are different from that used in several past studies 33,34 where the activation values are multiplied by gradients to produce heatmaps, however such heatmaps are prone to contamination by large predictor values and thus misleading the importance of specific regions 32 . Eq.…”
Section: Heatmapsmentioning
confidence: 99%